FPGA implementation of bilinear interpolation algorithm for CFA demosaicing - Rani, K. Sudha; Hans, W. Jino (2013 International Conference on Communications and Signal Processing (ICCSP), 2013)
Color Filter Array (CFA) is a mosaic of tiny color filters placed over the pixels of an image sensor to capture information. The most common filter is Bayer's filter. A Bayer filter arranges RGB color filters on a square grid of photo sensors. The color filters is used in single chip image sensors which is used in digital cameras, camcorders and scanners to create a color image. Digital still cameras (DSC) are widely used nowadays and it has a single chip CCD image sensor in order to reduce the cost. These single chip cameras use CF A to obtain different color information. Since only one component is available (Either R or G or B) at each pixel, the other two missing color components have to be estimated from the neighboring pixels. The process is called as CFA demosaicing. Demosaicing is a digital image process used to reconstruct full color image from the incomplete color samples. Various types of demosaicing algorithms are linear and bilinear interpolation, bicubic interpolation cubic spline interpolation, homogeneity directed demosaicing algorithm, higher order interpolation and higher order extrapolation etc. Bilinear interpolation algorithm for a 64*64 image is simulated in Xilinx.